2002
DOI: 10.1063/1.1473672
|View full text |Cite
|
Sign up to set email alerts
|

Relaxor and normal ferroelectric behavior in ordered thin films of PbSc0.5Nb0.5O3

Abstract: Epitaxial heterostructures of ordered perovskite PbSc0.5Nb0.5O3 thin films were grown by pulsed laser deposition using MgO and LaAlO3 single-crystal substrates, and La0.5Sr0.5CoO3 bottom electrode layers. The small-signal dielectric response of the heterostructures was measured in a broad range of temperatures (290–625 K) and frequencies (102–106 Hz). The contribution of the film–electrode interfaces was evaluated, and the true properties of the films were analyzed. Both relaxor and normal ferroelectric types … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…In SrTiO 3 films, the dielectric peak [5] is of relaxor nature [9]. Importantly, in epitaxial films of perovskite-type relaxors, strain has been found to enhance relaxor features, but not to induce the FE state [11]. Unexpectedly, the relaxorlike properties have been observed also in epitaxial films of FE BaTiO 3 and FE ðBa; SrÞTiO 3 [12,13].…”
mentioning
confidence: 66%
“…In SrTiO 3 films, the dielectric peak [5] is of relaxor nature [9]. Importantly, in epitaxial films of perovskite-type relaxors, strain has been found to enhance relaxor features, but not to induce the FE state [11]. Unexpectedly, the relaxorlike properties have been observed also in epitaxial films of FE BaTiO 3 and FE ðBa; SrÞTiO 3 [12,13].…”
mentioning
confidence: 66%
“…The theoretical misfit strain in a pseudomorphic PSN/ LSCO/MgO stack is very large [21,[31][32][33]. However, the misfit strain is efficiently relaxed in the grown epitaxial PSN/ LSCO/MgO heterostructures, as evidenced by XRD.…”
Section: Microstructure Of Psnmentioning
confidence: 98%
“…29 Moreover, it has been shown that the increasing tetragonal distortion is also associated with a gradual enhancement of the relaxor character of the dielectric permittivity. 40,41 It is worth noting that the ferroelectric phase transition in bulk PSN can be suppressed by the hydrostatic pressure. 42 In fact, the pressure induced lowering of the ferroelectric phase transition temperature T C is stronger than the pressure induced lowering of the temperature T m of the dielectric anomaly.…”
Section: Discussionmentioning
confidence: 99%